Relevansi Kompetensi Guru Menurut UU No 14 Tahun 2005 Dengan Ayat-Ayat Al-Qur’an Tentang Guru Dan Dosen - Mujib Ridlwan; Zakariyah Zakariyah (THE JOER: Journal Of Education Research, 2022)
Teachers or Lecturers are people who are very instrumental in the world of education and professional staff who are tasked with teaching, educating, and competent in educating students based on the Qur'an and the 1945 Constitution. The aim of the study is to describe and understand the relevance of teacher competence according to the verses in the Qur'an with Law No. 14 of 2005 concerning Teachers and Lecturers. This article uses a qualitative research method with a descriptive approach by analyzing and making conclusions from the data that has been obtained. The findings related to 1. Teacher and Lecturer competencies in the Qur'an are: a. QS. Al-Mujlah: 11, b. QS. Al-Qalam: 1-4, c. QS. Al-Nahl: 43-44 and d. QS. Al-Baqarah: 247. 2. Competency criteria that must be possessed by a teacher include: a. Mastering and utilizing information and communication technology for self-development and learning interests. b. Must have the qualities of patience, self-confidence, courage, enthusiasm, earnestness and never give up in carrying out their duties as educators. c. Fully responsible and have a high work ethic with his duties as an educator. d. Has a personality like the Prophet Muhammad SAW. 3. The relevance of the letter QS. Al-Mujlah: 11, QS. Al-Qalam: 1-4, QS. Al-Nahl: 43-44 and QS. Al-Baqarah: 247 with the Minister of National Education Regulation number 16 of 2007 concerning Teacher Competency Standards that there is a conformity related to teacher competence, namely; a) Personal competence, b) Pedagogic competence, c) Social competence and professional competence.